If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -6y + 2 = 3 + -10 + y Reorder the terms: 2 + 8y + -6y = 3 + -10 + y Combine like terms: 8y + -6y = 2y 2 + 2y = 3 + -10 + y Combine like terms: 3 + -10 = -7 2 + 2y = -7 + y Solving 2 + 2y = -7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 2y + -1y = -7 + y + -1y Combine like terms: 2y + -1y = 1y 2 + 1y = -7 + y + -1y Combine like terms: y + -1y = 0 2 + 1y = -7 + 0 2 + 1y = -7 Add '-2' to each side of the equation. 2 + -2 + 1y = -7 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = -7 + -2 1y = -7 + -2 Combine like terms: -7 + -2 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| 4z+7= | | y=6x-4 | | 2=n/3-5 | | 2x+10=2x-0.8 | | x(2x-1)(x+4)=0 | | x(2x-1)(x+4)=8 | | 15y^2-17y-4=0 | | n/6+12=11 | | 7y+4(y-6)=4(y+2)-2 | | x-5x=7x-9-x | | 14=7-n | | 4x^2-28x=15 | | 5a+5a=40 | | x-2=-2x+3+3.5 | | 2(3)-2= | | -2(t-5)+9t=5t-3 | | 60x-41=-17 | | (x+4)+(x+2)+x=(x+2)+x-22 | | 3(2x+3)-3=6x+6 | | 2m-2=3 | | 3+6n=-63 | | y*2+3=2(y-2) | | 4x^2+48x+143=0 | | 6x+3=6(x+4) | | b*b+b=2 | | q-5=12 | | 4b-4=3b+2 | | 5x-3y=45 | | 180+3a=2a-25 | | 4a+6=26 | | 34=-5-9t | | 40y+4-60y+12=200 |